Exploring the Relationships between Scientific Epistemic Beliefs, Science Teaching Beliefs and Science-Specific PCK among Pre-Service Kindergarten Teachers in China. Issue 1 (2nd January 2021) - Wu, Dandan; Liao, Ting; Yang, Weipeng; Li, Hui
ABSTRACT: Research Findings: This study aims to explore the relationships between Scientific Epistemic Beliefs (SEB), Science Teaching Beliefs (STB) and Science-specific Pedagogical Content Knowledge (Science-PCK) in preservice kindergarten teachers from China. Altogether 987 preservice teachers were randomly sampled from a teacher education institution and were invited to complete Scientific Epistemic Beliefs Scale, Teachers' Science Teaching Beliefs scale, and Science-PCK scale. Their personal information (such as age, gender and family income) was collected, and their work-orientated interest and anxiety were also surveyed. CFA and path analysis generated a model with excellent fit, CFI =.946, TLI =.886, NFI =.923, RMSEA =.045, X 2  = 29.864, df = 10, p <.001. This model indicated that: (1) SEB strongly predicted STB and Science-PCK; (2) Science teaching anxiety partially mediated the association between SEB and STB; (3) STB partially mediated the association between SEB and Science-PCK; and (4) STB was a full mediator between Year/SES/Interest and Science-PCK. Practice or Policy : ECE teacher education program should be improved to pay more attention to SEB and STB training and to cater to individual differences in terms of Anxiety and SES backgrounds.